C9orf72-associated SMCR8 protein binds in the ubiquitin pathway and with proteins linked with neurological disease - John L. Goodier (Acta Neuropathologica Communications, 2020)
Abstract A pathogenic GGGCCC hexanucleotide expansion in the first intron/promoter region of the C9orf72 gene is the most common mutation associated with amyotrophic lateral sclerosis (ALS). The C9orf72 gene product forms a complex with SMCR8 (Smith-Magenis Syndrome Chromosome Region, Candidate 8) and WDR41 (WD Repeat domain 41) proteins. Recent studies have indicated roles for the complex in autophagy regulation, vesicle trafficking, and immune response in transgenic mice, however a direct connection with ALS etiology remains unclear. With the aim of increasing understanding of the multi-functional C9orf72-SMCR8-WDR41 complex, we determined by mass spectrometry analysis the proteins that directly associate with SMCR8. SMCR8 protein binds many components of the ubiquitin-proteasome system, and we demonstrate its poly-ubiquitination without obvious degradation. Evidence is also presented for localization of endogenous SMCR8 protein to cytoplasmic stress granules. However, in several cell lines we failed to reproduce previous observations that C9orf72 protein enters these granules. SMCR8 protein associates with many products of genes associated with various Mendelian neurological disorders in addition to ALS, implicating SMCR8-containing complexes in a range of neuropathologies. We reinforce previous observations that SMCR8 and C9orf72 protein levels are positively linked, and now show in vivo that SMCR8 protein levels are greatly reduced in brain tissues of C9orf72 gene expansion carrier individuals. While further study is required, these data suggest that SMCR8 protein level might prove a useful biomarker for the C9orf72 expansion in ALS.